STUDENTS ADAPTIVE LEVEL TO THE NEW LEARNING STYLES AS A RESULTANT EFFECT OF COVID-19 - Adenike Aderogba Onojah; Amos Ochayi Onojah; Nasiru Ahmed Ala (Indonesian Journal of Learning and Instruction, 2022)
The recent covid-19 crisis had made it mandatory for schools to introduce new learning styles. However, the extent at which students will adapt to this new learning environment could differ as most are just being exposed to this context. This study therefore investigated the adaptive level of students to the new learning methods. The population comprised all students in Nigeria out of which 2500 respondents were sampled across the schools in Nigeria based on their accessibility. A researcher-developed questionnaire was used to gather data for the study. All ethical issues were put into consideration as none of the respondents were cohersed to participate in this study. Means were used to answer the research questions while hypothesis one was tested using Man-U Whiteny at 0.05 significance level. The findings established that majority of the students initially find the distance education uneasy and data consuming. There was significant difference between public and private students’ adaptive level to the new learning methods. The study concluded that students are getting used to the new learning style introduced by their various schools because they have only that choice to learn with. It was therefore recommended that school administrators and teachers should continue encouraging students to use this learning style introduced as they may find it uneasy to use. The learning style adopted should also be such that attracts the learners’ attention.Keywords: COVID-19; students’ adaptive level; learning styles; resultant effect.